A Decomposition of Multidimensional Economic Well-being: an application to Spanish regions - Jesus Perez-Mayo; Carlos Díaz-Caro (European Regional Science Association (ERSA), 2015)
The aim of this paper is to analyze the evolution of well-being changes due to, on one side, the changes in the weighting scheme and, on the other, changes in the indicators along the time. An alternative methodology is proposed in this paper that allows one to decompose a multidimensional index of economic well-being by distinguishing such effects from some dimensions as adjusted consumption, real wealth, inequality and economic security. The analysis is performed between 2000 and 2010 for all the Spanish regions. The main results show the relevance of differentiating between both components of change.
Keywords: I31; I32; 330; well-being; decomposition; regional inequalities